2007
DOI: 10.1037/1099-9809.13.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of the Intragroup Marginalization Inventory.

Abstract: This study reports the development and validation of the Intragroup Marginalization Inventory (IMI). The IMI consists of three scales that assess the extent to which an individual perceives interpersonal distancing from family, friends, and ethnic group community members. Intragroup marginalization is defined as the interpersonal distancing that occurs when an acculturating individual is believed to exhibit behaviors, values, and beliefs that are outside the heritage culture's group norms. Intragroup marginali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(147 citation statements)
references
References 56 publications
3
141
1
Order By: Relevance
“…A study on the IMIFamily's construct validity with Latino, Asian American, and African American students found that it is moderately correlated with established measures of social negative exchange with family members (Castillo et al 2007). Internal reliability estimates for this study's sample for Homeostatic Pressure, Linguistic Expectations, Accusation of Assimilation, and Discrepant Values were .75, .88, .86, and .61, respectively.…”
Section: Family Intragroup Marginalizationmentioning
confidence: 95%
See 3 more Smart Citations
“…A study on the IMIFamily's construct validity with Latino, Asian American, and African American students found that it is moderately correlated with established measures of social negative exchange with family members (Castillo et al 2007). Internal reliability estimates for this study's sample for Homeostatic Pressure, Linguistic Expectations, Accusation of Assimilation, and Discrepant Values were .75, .88, .86, and .61, respectively.…”
Section: Family Intragroup Marginalizationmentioning
confidence: 95%
“…Ethnic groups have their own distinct cultural identity and as a group member's behavior begins to move away from the maintenance of that cultural identity and begins to approximate that of the dominant culture, the acculturating member may perceive that other group members are imposing social sanctions against them, thus marginalizing them from the group. When a member of said group is observed displaying behaviors or attitudes outside of the group norm, other members may perceive this behavior as a threat to the group's distinct identity (Castillo et al 2007). Interpersonal distancing ranges from questioning of loyalty to the ethnic group to social ostracism.…”
Section: Acting Whitementioning
confidence: 98%
See 2 more Smart Citations
“…The influence of family dynamics and the strategies each partner utilises can lead to conflict (Morrison & James, 2009). Conflict may occur when a low acculturated partner expects the other partner, who has already adapted to the dominant host culture, to continue to follow premigration values and traditions (Castillo, Conoley, Brossart, & Quiros, 2007). A husband or wife who is less acculturated may perceive the behaviour of the more highly acculturated partner as a threat, thereby increasing their own level of acculturative stress, which in turn leads to conflict (Lee & Liu, 2001).…”
Section: Marital Relationshipsmentioning
confidence: 99%